Perbandingan Jumlah Trombosit pada Pasien COVID-19 dengan Kadar Glukosa yang Berbeda - Octavira, Imanta Alifia; Agrijanti, Agrijanti; Srigede, Lalu; Zaetun, Siti (Jurnal Kesehatan Andalas, 2022)
Hyperglycemia has increased arachidonic acid thromboxane which is an effective ingredient in platelet activation. Thrombocytopenia in COVID-19 patients occurs through a variety of mechanisms, such as uncontrolled production of cytokines destroying bone marrow progenitor cells, direct inhibition of hematopoiesis viral infection of the bone marrow, increase in autoantibodies and immune complexes that cause platelet destruction, and lung injury that causes platelet aggregation and consumption of platelets so that platelets in the circulation are reduced. Objectives: To analyzed the ratio of platelet counts in COVID-19-positive patients who had different blood glucose levels. Methods: This research used secondary data, with types of analytical observational research as well as comparative study approaches. Statistical tests were conducted using an independent samples t-test with a confidence level of 95%. Results: The average platelet count was normal, but a low platelet count of 3.30% was obtained with normal blood glucose levels and a high platelet count of 2.20% with normal blood glucose levels, with a significance value of platelet count with normal blood glucose levels of 0.790 and platelet counts with blood glucose levels above normal which is 0.791 with a confidence level of 95%. Conclusion: There was no significant difference between the platelet count in COVID-19 patients with normal and above normal blood glucose levelsKeywords: blood glucose, platelets, COVID-19